Self-Efficacy in the context of learning strategies: A systematic literature review - Rosiyanti, Hastri; Priatna, Nanang; Turmudi (Indonesian Research Journal in Education |IRJE|, 2025)
Self-efficacy is a crucial psychological factor influencing student success, particularly within effective learning strategies. Confidence in one’s abilities affects motivation, engagement, self-regulation, and academic achievement. This research aims to explore the distribution of education types in learning strategies across various countries, investigate key points of self-efficacy in education, define its main categories, and analyze research subject distribution in educational studies. The research methodology used is a systematic literature review (SLR), following PRISMA guidelines and using data from the Scopus database. Of the 40 articles, 16 were selected for further analysis. The findings show that most studies focus on higher education, while primary and secondary education receive less attention. Research is concentrated in countries like Malaysia, Turkey, and Iran. Key results reveal two main categories of self-efficacy: general beliefs and contextual-situational beliefs. The conclusion highlights the need for learning strategies supporting self-efficacy across all educational levels to enhance student learning outcomes.